Dabigatran and Wet AMD, Results From Retinal Pigment Epithelial Cell Monolayers, the Mouse Model of Choroidal Neovascularization, and Patients From the Medicare Data Base - Akter, Tanjina; Annamalai, Balasubramaniam; Obert, Elisabeth; Simpson, Kit N.; Rohrer, Bärbel (Frontiers in Immunology, 2022)
Background: Age-related macular degeneration (AMD), the leading cause of irreversible blindness in elderly Caucasian populations, includes destruction of the blood-retina barrier (BRB) generated by the retinal pigment epithelium-Bruch’s membrane complex (RPE/BrM), and complement activation. Thrombin is likely to get access to those structures upon BRB integrity loss. Here we investigate the potential role of thrombin in AMD by analyzing effects of the thrombin inhibitor dabigatran. Material and Methods: MarketScan data for patients aged ≥65 years on Medicare was used to identify association between AMD and dabigatran use. ARPE-19 cells grown as mature monolayers were analyzed for thrombin effects on barrier function (transepithelial resistance; TER) and downstream signaling (complement activation, expression of connective tissue growth factor (CTGF), and secretion of vascular endothelial growth factor (VEGF)). Laser-induced choroidal neovascularization (CNV) in mouse is used to test the identified downstream signaling. Results: Risk of new wet AMD diagnosis was reduced in dabigatran users. In RPE monolayers, thrombin reduced TER, generated unique complement C3 and C5 cleavage products, led to C3d/MAC deposition on cell surfaces, and increased CTGF expression via PAR1-receptor activation and VEGF secretion. CNV lesion repair was accelerated by dabigatran, and molecular readouts suggest that dabigatran targets include CTGF and VEGF, but not the complement system. Conclusions: This study provides evidence of association between dabigatran use and reduced exudative AMD diagnosis. Based on the cell- and animal-based studies, we suggest that thrombin modulates wound healing and CTGF and VEGF expression, making dabigatran a potential novel treatment option in AMD.